Evolution under strong balancing selection: how many codons determine specificity at the female self-incompatibility gene SRK in Brassicaceae? - Castric, Vincent (BioMed Central, 2007)
BACKGROUND: Molecular lock-and-key systems are common among reproductive proteins, yet their evolution remains a major puzzle in evolutionary biology. In the Brassicaceae, the genes encoding self-incompatibility have been identified, but technical challenges currently prevent detailed analyses of the molecular interaction between the male and female components. In the present study, we investigate sequence polymorphism in the female specificity determinant SRK of Arabidopsis halleri from throughout Europe. Using a comparative approach based on published SRK sequences in A. lyrata and Brassica, we track the signature of frequency-dependent selection acting on these genes at the codon level. Using simulations, we evaluate power and accuracy of our approach and estimate the proportion of codon sites involved in the molecular interaction. RESULTS: We identified several members of the S-gene family, together with 22 putative S-haplotypes. Linkage to the S-locus and the presence of a kinase domain were formally demonstrated for four and six of these haplotypes, respectively, and sequence polymorphism was extremely high. Twenty-five codons showed signs of positive selection in at least one species, and clustered significantly (but not exclusively) within hypervariable regions. We checked that this clustering was not an artifact due to variation in evolution rate at synonymous sites. Simulations revealed that the analysis was highly accurate, thus providing a reliable set of candidates for future functional analyses, but with an overall power not higher than 60 %. Assuming similar power, we infer from our results that about 23% of all codons in the S-domain may actually be involved in recognition. Interestingly, while simulations demonstrated that this comparison remained reliable even at very high levels of divergence, codons identified in Brassica had higher posterior rates of non-synonymous to synonymous substitutions than codons identified in A. halleri or A. lyrata, possibly suggesting more intense selection in Brassica. CONCLUSION: The signature of balancing selection can be identified reliably at the codon level even in cases of very high sequence divergence, provided that a sufficiently large set of sequences are analyzed. Altogether, our results indicate that a large proportion of codons may be involved in recognition and confirm the particular importance of hypervariable regions. The more intense signature of positive selection detected in Brassica suggests that allelic diversification in this genus was very recent, possibly following a recent demographic bottleneck.